Turn-Taking Strategies in Happy Sad Confused: Crafting an Interactive and Engaging Talk Show Experience - Frevy Maharani; Dadan Firdaus; Ice Sariyati (UIN Salatiga, 2025)
Turn-taking manages mechanical speaking turns and creates a cooperative, dynamic, and entertaining conversation. Therefore, creating pleasant and engaging experiences allows participants to express their ideas confidently. Thus, this study investigates how such an experience is facilitated by the turn-taking mechanism in Happy Sad Confused and identifies how markers are used as strategies in conversational dynamics. This study used a descriptive qualitative method and Stenström's (1994) theory related to turn-taking strategies. The data were collected using Jefferson's (2009) transcription approach. The results of this study showed that the interaction between Josh Horowitz and Henry Cavill demonstrated a successful turn-taking mechanism to promote compelling discussion, allowing Henry Cavill to disclose emotive and in-depth work experiences. So, turn-taking also enriched conversational dynamics in a talk show scenario. Markers significantly contributed to maintaining the natural flow of communication and smooth transitions to keep the conversation rhythm. The most dominant marker by filled pauses (e.g., “ǝ:m”, “uh”) was 47 times. Overall, turn-taking maintained interesting communication. Speakers could use suitable tactics and markers to enable meaningful interactions, making talks more dynamic and entertaining for participants and viewers.